Creativity : theories and themes: research, development, and practice - Runco, Mark A. (Burlington : Elsevier Science, 2014)
An integrative introduction to the theories and themes in research on creativity, the second edition of Creativity is both a reference work and text for courses in this burgeoning area of research. The book begins with a discussion of the theories of creativity (Person, Product, Process, Place), the general question of whether creativity is influenced by nature or nurture, what research has indicated of the personality and style of creative individuals from a personality analysis standpoint, and how social context affects creativity. This wide-ranging work then proceeds to coverage of issues such as gender differences, whether creativity can be enhanced, if creativity is related to poor mental or physical health, and much more. The book contains boxes covering special interest items, including one-page biographies of famous creative individuals, and activities for a group or individual to test or encourage creativity, as well as references to Internet sites relating to creativity.
Cognition and Creativity -- Developmental Trends and Influences on Creativity -- Biological Perspectives on Creativity -- Health and Clinical Perspectives -- Social, Attributional, and Organizational Perspectives -- Educational Perspectives -- History and Historiometry -- Culture and Creativity -- Personality and Motivation -- Creativity and Politics -- Creativity and Philosophy -- Enhancement and the Fulfillment of Potential -- Conclusion: What Creativity is and What it is Not.
Print version record.
Includes bibliographical references and index.
Keywords: Creative ability; Creation (Literary, artistic, etc.); Creative ability -- Psychological aspects; PSYCHOLOGY -- Cognitive Psychology; SCIENCE -- Cognitive Science; Creation (Literary, artistic, etc.); Creative ability; Creative ability -- Psychological aspects; Electronic books; Electronic books